A New Approach to the Synthesis of Benzo[c][1,7]naphthyridin-4(3H)-ones - Kulakov, Ivan V.; Shatsauskas, Anton L.; Matsukevich, Mariya V.; Palamarchuk, Irina V.; Seilkhanov, Tulegen M.; Gatilov, Yuriy V.; Fisyuk, Alexander S. (Synthesis, 2017)
A simple and efficient approach has been developed for the synthesis of previously inaccessible 6-arylbenzo[c][1,7]naphthyridin-4(3H)-ones, which is based on the interaction of 3-amino-6-methyl-4-arylpyridin-2(1H)-ones and aromatic aldehydes in a strong acidic media (trifluoroacetic, phosphorous or polyphosphorous acids) under heating. The initial imine derivatives undergo Pictet–Spengler condensation to form intermediate 6-aryl-5,6-dihydrobenzo[c]-1,7-naphthyridin-4(3H)-ones, which are oxidized by atmospheric oxygen to give 3-amino-6-methyl-4-arylpyridin-2(1H)-ones as the final products.
Keywords: naphthyridines; pyridines; Pictet–Spengler reaction; intramolecular cyclization; X-ray structural analysis